Natural Organic Matter Degradation Using Combined Process of Ultrasonic and Hydrogen Peroxide Treatment - Pourzamani, Hamidreza; Majd, Amir Masoud Samani; Attar, Hossein Movahedian; Bina, Bijan (Anuário do Instituto de Geociências, 2017)
The purpose of this study was to explore and examine an advance oxidation process using ultrasonic (US)/H2O2 as a potential treatment and removal of humic acid (HA). The US power, HA concentration and H2O2 concentration enhanced removal process was performed by varying the irradiation time, the preliminary experiments demonstrated that natural organic matter (NOM) and HA removal was influenced by the power, HA concentration and time of sonication. The optimum conditions for HA and NOM removal were achieved by US irradiation of 110 W power, at 20 min contact time, and 20 mg.L-1 of HA concentration. Likewise, the optimum conditions for HA and NOM removal with hydrogen peroxide were obtained at 120 min time and 10Ã—10-3 mol.L-1 of H2O2. The results indicated a strong capacity of sonication for NOM and HA removal, therefore by adding H2O2 to the aqueous solution increased NOM and HA removal by US. The HA removal efficiency of US/H2O2 (91.5%) was more than US (69.3%) and H2O2 (20%). US/H2O2 system proved to be the most effective. The sonochemical degradation with US/H2O2 can be an efficient method to remove the NOM from aqueous solution and may be a realistic possibility for large-scale treatment.